2020
DOI: 10.33258/birci.v3i2.954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19’s Pandemic on the Economy of Indonesia

Abstract: COVID-19 is a global health problem including in Indonesia. The increased case of COVID-19 proved to have quite a significant impact on the economy globally which may have affected stability in Indonesia. This method of collecting data is a method of study literature with secondary data types. Data is taken from the Internet with respect to the validity of information such as government official information, official online sites and processed results of valid data. After obtaining the existing reference, a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
206
1
81

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(290 citation statements)
references
References 2 publications
2
206
1
81
Order By: Relevance
“…Shifting the focus from global to domestic, (Susilawati et al, 2020) studied the impact of Covid-19 on Indonesian economy. The study concluded that the Covid-19 has significant adverse impact on different sectors of Indonesian economy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifting the focus from global to domestic, (Susilawati et al, 2020) studied the impact of Covid-19 on Indonesian economy. The study concluded that the Covid-19 has significant adverse impact on different sectors of Indonesian economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The manuscript proposed that the pandemic will cause global economic recession. Some other studies have analyzed the impact of Covid-19 on economies of different countries and regions (Giulietti, 2020;Mahendra Dev & Sengupta, 2020;Susilawati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Berbagai bentuk kebijakan pembatasan aktifitas masyarakat yang ditempuh untuk mencegah penyebaran COVID-19 otomatis menghambat dan menekan pertumbuhan ekonomi. Beberapa sektor yang terkena dampak akibat pandemic Covid-19 antara lain transportasi, pariwisata, perdagangan, pendidikan, kesehatan, dan yang paling serius adalah rumah tangga (Susilawati et al, 2020). Terhambatnya beberapa sektor diatas menyebabkan berkurangnya tenaga kerja yang dibutuhkan sehingga banyak perusahaan yang melakukan pemutusan hubungan kerja (PHK).…”
Section: Dampak Sosial Ekonomi Akibat Pandemi Covid-19unclassified
“…This reduction in workforce has also resulted in increased unemployment and poverty, especially in rural areas. The Indonesian government in this condition has tried to accelerate state spending and divert the state budget for handling, preventing Covid-19 and overcoming the impact due to the implementation of this large-scale social restriction [12].…”
Section: Making Emergency Law and Using Village Fundmentioning
confidence: 99%